Absorptive Capacity: Scale Development and Implications for Future Research - Chauvet, Vincent (Management international / International Management / Gestiòn Internacional, 2014)
In response to recent criticism concerning Absorptive CAPacity (ACAP) research we developed a new measure of this concept. Unlike past empirical studies that used proxies, this work tries to take advantage of past research in considering ACAP as a multilevel and multidimensional construct. This article, based on a large literature review, tries to fill this gap in developing and testing a scale of ACAP, composed of four factors and 18 items, that meets main validity and reliability criteria. We believe this research contributes to develop our understanding concerning ACAP and hope it facilitates the emergence of a new approach of the concept.